2008
DOI: 10.1007/s11082-009-9329-7
|View full text |Cite
|
Sign up to set email alerts
|

The design of low-loss curved waveguides

Abstract: A procedure for the design of low-loss continuous curvature waveguide bends, for use in integrated photonic circuits, is presented. The design employs the scalar finite element method and a technique for drawing waveguide bends based on their curvature. The finite difference beam propagation method is used to determine the power lost along the length of the waveguide structures. This new method allows the design of waveguide bends with lower loss than can be obtained by conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…These transition losses are inversely proportional to the square of the radius of curvature, ROC 2 [49]. Bends with decreasing ROC at intersections to straight waveguide sections [50] or bend-offsets [51] reduce these mode conversion losses while keeping the effective bend radius, i.e., the space required for a low-loss bend, almost unaffected. In this work, we characterize waveguides with circular bends only in order to determine the minimum bend radius.…”
Section: Bendsmentioning
confidence: 99%
“…These transition losses are inversely proportional to the square of the radius of curvature, ROC 2 [49]. Bends with decreasing ROC at intersections to straight waveguide sections [50] or bend-offsets [51] reduce these mode conversion losses while keeping the effective bend radius, i.e., the space required for a low-loss bend, almost unaffected. In this work, we characterize waveguides with circular bends only in order to determine the minimum bend radius.…”
Section: Bendsmentioning
confidence: 99%
“…It has been shown that in the study of curved waveguides, a conformal transformation may be applied to the waveguide which results in the addition of a linear term to the refractive index [56][57][58][59]. This is illustrated for a waveguide with constant index of refraction in Fig 2 . FIG.…”
Section: Fig 1: Local Bending Radius Of a Curvementioning
confidence: 99%
“…Low-loss curved waveguides can be achieved by introducing non-linear curvatures [11]. However, if all the arrayed waveguides exhibit different nonlinear bends, the phase errors introduced by small bending radii can reach significant levels.…”
Section: The Identical-bend Designmentioning
confidence: 99%